BaTiO3 Nanoparticle-Induced Interfacial Electric Field Optimization in Chloride Solid Electrolytes for 4.8 V All-Solid-State Lithium Batteries - Xiao, Qingmei; Huang, Shiming; Liang, Donghao; Liu, Cheng; Zhang, Ruonan; Li, Wenjin; Liu, Guangliang Gary (Nano-Micro Letters, 2025)
Chloride-based solid electrolytes are considered promising candidates for next-generation high-energy–density all-solid-state batteries (ASSBs). However, their relatively low oxidative decomposition threshold ( 4.2 V vs. Li+/Li) constrains their use in ultrahigh-voltage systems (e.g., 4.8 V). In this work, ferroelectric BaTiO3 (BTO) nanoparticles with optimized thickness of 50–100 nm were successfully coated onto Li2.5Y0.5Zr0.5Cl6 (LYZC@5BTO) electrolytes using a time-efficient ball-milling process. The nanoparticle-induced interfacial ionic conduction enhancement mechanism contributed to the preservation of LYZC’s high ionic conductivity, which remained at 1.06 mS cm−1 for LYZC@5BTO. Furthermore, this surface electric field engineering strategy effectively mitigates the voltage-induced self-decomposition of chloride-based solid electrolytes, suppresses parasitic interfacial reactions with single-crystal NCM811 (SCNCM811), and inhibits the irreversible phase transition of SCNCM811. Consequently, the cycling stability of LYZC under high-voltage conditions (4.8 V vs. Li⁺/Li) is significantly improved. Specifically, ASSB cells employing LYZC@5BTO exhibited a superior discharge capacity of 95.4 mAh g−1 over 200 cycles at 1 C, way outperforming cell using pristine LYZC that only shows a capacity of 55.4 mAh g−1. Furthermore, time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy analysis revealed that Metal-O-Cl by-products from cumulative interfacial side reactions accounted for 6% of the surface species initially, rising to 26% after 200 cycles in pristine LYZC. In contrast, LYZC@5BTO limited this increase to only 14%, confirming the effectiveness of BTO in stabilizing the interfacial chemistry. This electric field modulation strategy offers a promising route toward the commercialization of high-voltage solid-state electrolytes and energy-dense ASSBs. Highlights: 1 Time efficient ball milling achieves uniform BaTiO3 ( coating without sacrificing ionic conductivity (1.06 mS cm−1). 2 Ferroelectric BTO coating suppresses Li2.5Y0.5Zr0.5Cl6 (LYZC decomposition at 4.8 V via electric field modulation, enabling 76% capacity retention after 150 cycles. 3 BTO effectively minimizes the formation of interfacial ZrCl3O /YCl2O byproducts and mitigates the irreversible phase transition of single crystal NCM811 (SCNCM811), thereby improving the compatibility between LYZC and SCNCM811.